PANCASILA PERSPECTIVE MARRIAGE SYSTEM: HARMONY OF NATIONAL VALUES IN FAMILY INSTITUTIONS - Jalil, Dul; Fariduddin, Ecep Ishak; Yasir, Muhammad Farhan Qurroto (JURNAL ILMU SYARIAH, 2024)
This article attempts to explain that marriage is defined as a spiritual and physical bond between a man and a woman to achieve happiness. However, in reality, many marriages are forced, resulting in unhappiness. This goes against the purpose of marriage stated in the law. The inclusion of the phrase "Belief in the Almighty God" in the definition of marriage in Article 1 of Law no. 1 of 1974 shows that marriage is not only a personal matter, but also a legal relationship that contains religious values based on Pancasila as the Indonesian philosophy of life. The marriage law explains that marriage is a spiritual and physical bond between a man and a woman, but this explanation is different from that regulated in the Civil Code, especially Book III. This difference is the background for this research. The purpose of this research is to find out and explain that there should be no substantivedifferences between the 1974 Marriage Law and the Civil Code, especially Book III. This is necessary so that the public gets legal certainty, both in terms of the Marriage Law and the Civil Law. This research uses qualitative methods, with a type of library research that is based on library data or documentation that is relevant to the title of this research. The research results show that there is legal uncertainty in the field of marriage law, which is caused by the provisions in Article 66 of Law No. 1 of 1974 which states that colonial product legal provisions do not apply, even though the Civil Code is also a colonial product. Therefore, there needs to be legal certainty to avoid confusion in society.